E-khairat system - Nur Faraelya Azira, Saman (2019)
With the growth of technology, people nowadays prefer to find and use something that can help and make their daily life become easier. As a Muslim, we also need a system or a web-based system that can becomes a platform that will be able to manage for Muslim death which called e-khairat. Khairat derive from Arabic word which mean charity such as donation and so on. There are many types of khairat such as khairat that manage Muslim death in order to complete the demands of fardhu kifayah. This e-khairat system is develop in order to replace the existing manual system due to limitations of manual system. This objective of this e-khairat system is to develop a web-based system that will be able to manage Muslim death matters and update to the user for latest information about Muslim death. Rapid Application Development (RAD) is the methodology that been used to develop this system. This RAD consist of four stages or phases which are requirement planning stages, user design stages, rapid construction stages and transition stages. The proposed e-Khairat system is expected to inform and update the community about the Muslim death. In a nutshell, this e-Khairat system help to provides an efficient solution to manage this e-Khairat system.